Galectin‐9: Diverse roles in hepatic immune homeostasis and inflammation. Issue 1 (27th May 2017) - Golden‐Mason, Lucy; Rosen, Hugo R.
Abstract : Glycan‐binding proteins, which include galectins, are involved at all stages of immunity and inflammation, from initiation through resolution. Galectin‐9 (Gal‐9) is highly expressed in the liver and has a wide variety of biological functions in innate and adaptive immunity that are instrumental in the maintenance of hepatic homeostasis. In the setting of viral hepatitis, increased expression of Gal‐9 drives the expansion of regulatory T cells and contraction of effector T cells, thereby favoring viral persistence. The dichotomous nature of Gal‐9 is evident in hepatocellular carcinoma, where loss of expression in hepatocytes promotes tumor growth and metastasis, whereas overexpression by Kupffer cells and endothelial cells inhibits the antitumor immune response. In nonalcoholic fatty liver disease, Gal‐9 is involved indirectly in the expansion of protective natural killer T‐cell populations. In ischemic liver injury, hepatocyte‐derived Gal‐9 is both diagnostic and cytoprotective. In drug‐induced acute liver failure, plasma levels correlate with outcome. Here, we offer a synthesis of recent and emerging findings on Gal‐9 in the regulation of hepatic inflammation. Ongoing studies are warranted to better elucidate the pathophysiology of hepatic immune‐mediated diseases and to develop new therapeutic interventions using glycan‐binding proteins. (Hepatology 2017;66:271–279).